Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1097/pts.0000000000000276
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Safe Practices in Administering Pro re nata Medications in a Rural Hospital

Abstract: Developing and implementing a policy for safe pro re nata medications practices became a priority when 1 nurse questioned a regularly occurring double-range narcotic order. This article describes how double-range medications can compromise patient safety and how a small rural hospital with minimal resources was able to develop an interdisciplinary practice standard to ensure safe medication practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The safety of PRN medicines management is influenced by healthcare professionals’ knowledge and skills, and the healthcare culture ( Morkunas et al, 2016 ). The decision for the use of PRN medications are taken in collaboration with the physician, nurse, patient, and families, but it is accompanied by the risk of errors due to their distinct interpretations of the medication process ( Hogan et al, 2019 ). Ambiguities in PRN medicines management including indication for prescription, method of administration, and complete documentation can adversely impact patient care outcomes, increase the risk of polypharmacy, adverse drug events, and abuse ( Friedman et al, 2012 ; Oh et al, 2014 ; Hammer et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The safety of PRN medicines management is influenced by healthcare professionals’ knowledge and skills, and the healthcare culture ( Morkunas et al, 2016 ). The decision for the use of PRN medications are taken in collaboration with the physician, nurse, patient, and families, but it is accompanied by the risk of errors due to their distinct interpretations of the medication process ( Hogan et al, 2019 ). Ambiguities in PRN medicines management including indication for prescription, method of administration, and complete documentation can adversely impact patient care outcomes, increase the risk of polypharmacy, adverse drug events, and abuse ( Friedman et al, 2012 ; Oh et al, 2014 ; Hammer et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, rural primary care has unique challenges, often involving complex medical cases and limited resources [6,[11][12][13][14][15][16][17]. To tackle these problems, previous studies have suggested various approaches, such as strengthening multiprofessional collaboration [18][19][20][21][22][23], establishing remote pharmacy services [18,19], and developing public health programs aiming at medication process evaluation and enhanced safety of care providers [24,25]. To systematically control the risks associated with the medication process, rural primary care units could bene t from introducing proactive approaches, such as medication safety self-assessment (MSSA), to uncover the central risk points of care [16].…”
mentioning
confidence: 99%